Penerapan Mobilisasi Dini terhadap Penurunan Intensitas Nyeri Post Sectio Caesarea di RS PKU Muhammadiyah Karanganyar - Novita Dwi Safitri; Annisa Andriyani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background: One of the effects that occurs after Sectio Caesarea surgery is complaints of pain. Data from the World Health Organization (WHO) SC prevalence is 46% in China and 25% in Asia, Europe and Latin America. Based on 2021 RISKESDAS data, the number of deliveries using the Sectio Caesarea method in Indonesia is 17.6%. The data obtained at PKU Muhammadiyah Hospital included 1045 mothers giving birth by Sectio Caesarea. Post SC pain data is mostly on the moderate pain scale with 66.0%, mild pain with 25.7%, and severe pain with 7.7%. One non-pharmacological intervention is providing early mobilization measures. Objective: To determine the results of implementing early mobilization measures to reduce the intensity of Post Sectio Caesarea pain. Method: Descriptive observational research using a case study method carried out by 2 respondents from Post SC mothers who underwent early mobilization in the first 6 hours after caesarean section until the third day. Results: The pain scale in respondents after early mobilization was on the mild pain scale. Conclusion: There is a reduction in pain for Post Sectio Caesarea mothers by early mobilization.